Experiencing Transformative Learning: An Autoethnographic Journey through Ethical Dilemma Story Pedagogy (EDSP) - Pandey, Kashiraj (Bodhi: An Interdisciplinary Journal, 2019)
I believe our cultural heritage has so much potential for creating new forms of knowing about the self, others, community, and environment while also revealing the interconnected spaces and realities that reside between cultures and people. The Nepalese heritage encompasses through a rich tradition of narratives in storying. For the purpose of present research, I composed two ethical dilemma stories and discussed them in classrooms with a critically reflective understanding of the subject matter where I utilised the local, lived contexts and characters from the Nepalese society. The results have shown that this study, with the use of ethical dilemma stories as a key tool to interact with the research participants, gave sufficient challenges and possibilities for transformative learning. Therefore, the aim of this paper is to explore the unification of my personal, professional, and cultural spheres that are focused on the importance of transformative learning using an autoethnographic methodology. The paper also tries to document my lived experiences through stories as the understanding of my own self, other selves, and cultures around me.